Evolving demographics of eligible patient population can impact enrollment of a biomarker clinical study - Sara A. Vettleson-Trutza; Vanessa K. Pazdernik; Joseph H. Skalski; Melissa R. Snyder; Yifei K. Yang (PLoS ONE, 2025)
In a prospective clinical study to better understand how biological markers can improve diagnosis of and prognosis for asthmatic and atopic conditions, we contacted over 3500 eligible patients and observed noticeable differences in the range of their likelihood to enroll based on gender (3.8–13.4%), race and ethnicity (4.8–29.8%), and distance to study site (1.1–29.2%). Both the eligible patients and enrolled participants exhibited a more diverse racial and ethnic composition compared to local population demographics. Based on the eligible patients that the study team contacted (“eligible patients”, n = 3648) and those who agreed to enroll (“enrolled participants”, n = 454), we analyzed the gender, age, race and ethnicity composition of the groups, together with their proximity to the study site. Living close to the study site was the largest contributor to a patient's decision to enroll for both adults (odds ratio OR: 2.26, 95% confidence interval CI: 1.64–3.15, p < 0.001) and children (OR: 2.59, 95% CI: 1.67–4.41, p < 0.001). We also observed that patients from White and non-Hispanic racial and ethnic background were more likely to participate in the study among both pediatric (OR: 1.51, CI: 0.92–2.62, p = 0.122) and adult patients (OR: 1.81, CI: 1.18–2.89, p = 0.009). Eligible patients of female gender were also more likely to enroll in both adult (OR: 1.53, CI: 1.16–2.05, p = 0.003) and pediatric groups (OR: 2.14, CI: 1.42–3.22, p < 0.001). Overall, the pediatric patients (18 years old or younger) were much less willing to participate in the clinical biomarker study. Nonetheless, as they age, the enrollment likelihood increased accordingly (5 years OR: 1.71, CI, 1.32–2.21, p < 0.001). The eligible patient population of the study reflected the evolving demographics and different disease prevalence for asthma and other allergic diseases in adult and pediatric groups. These factors in turn influenced the composition of the enrolled participants.